Climate change, disability, and physical and rehabilitation medicine: A call for inclusive health action - Amatya, Bhasker; Khan, Fary (Bangabandhu Sheikh Mujib Medical University Journal, 2025)
Background: Climate change is an escalating global health emergency with widespread and disproportionate effects on populations. Despite representing over one billion individuals worldwide, people with disabilities (PwD) remain largely overlooked in climate adaptation and health planning. The health consequences of climate change for PwD are multifaceted and profound. This article aims to elaborate on the intersection of climate change and disability, explore the disproportionate impacts of climate change on PwD, emphasizing the pivotal role of Physical and Rehabilitation Medicine (PRM) professionals. Methods: This narrative review synthesizes expert perspectives to examine the intersection of climate change, disability, and health. A focused review of literature identified key themes and policy gaps, complemented by conceptual analysis highlighting the implications for PRM. Results: The complex interplay between climate change and disability is shaped by environmental stressors, health system disruptions, and pre-existing functional limitations. Evidence suggests that during climate-related events, PwD experience disproportionate impacts, including heightened morbidity, barriers to accessing essential services, and greater socio-economic and psychosocial vulnerability. PRM professionals are uniquely positioned to respond to the challenges of climate change through their expertise in functional restoration, long-term care, and disability-inclusive health services. However, rehabilitation remains underrepresented in many national and international climate response frameworks. The integration of rehabilitation into climate-resilient health systems requires all-inclusive governance, adaptive infrastructure, workforce capacity building, disability-focused research, and strengthened global partnerships. Conclusion: There is an urgent need to embed rehabilitation within climate change policies to ensure equitable, sustainable, and inclusive health systems. PRM professionals have a pivotal role in shaping and implementing these strategies, advocating for the rights and needs of PwD in the evolving climate crisis. A structured roadmap for climate-resilient, rehabilitation-inclusive health systems is essential to achieve health equity and resilience for all.